Traffic System Management by Means of Traffic Policy Implementation - Perić, Teodor; Bišević, Azra; Radačić, Željko (Promet - Traffic&Transportation, 2003)
As an active relation of the government towards the trafficsystem the traffic policy represents a correction measure of marketregulation of the relations within the traffic system and therelation of the traffic system with the environment due to theimperfection of the traffic market. Consistent traffic policy, aspart of the economic policy, assumes a clear definition of thetraffic policy goals, measures, and instruments as well as taskmanagers to realise the set goals. These are the preconditionsfor successful implementation of the traffic policy.